Agama dan Moral dalam Pembentukan Substansi dan Struktur Hukum - Rahmaningsih, Aziza Aziz; Rizqi, Retanisa (Universitas Islam Negeri Raden Intan Lampung, 2022)
Religious and moral relations are interrelated in the formation of a country's legal system. Religion is the initial foundation for building a moral society. In this way, religion, morals, and the state cannot be separated. A law becomes empty if it is not imbued with morality. Likewise with religion which gives color to the law to base substantive values on the public good and the upholding of justice, so that religion and morals can become elements in the development of the aspired law. This study aims to determine whether religion and morals have a role in the formation of legal substance and structure. This research is normative, studying the legal system with library research. The approach used is a historical approach, examining and studying developments regarding religion, morals, and the legal system. The study's findings indicate that the presence of religion and morality in human life has a nature, has an ontological function to regulate social life, and religion can substantively influence behavior in the formation of legal substance and structure. Morality and religion have a significant impact on the substantive formation of law. Law is formed on the basis of morality, so the effectiveness of legal products will be good, so that religion and morality create humanist and liberated laws that will help solve problems that exist in society. This study concludes that religion and morals influence the formation of substantive legal thinking and legal structure. The existence of religious and moral influences provides inspiration for the development of legal science and plays a role in creating a humanist and liberating law.